Three-dimensional modeling and time-delay stability analysis for robotics docking simulation. (November 2019) - Sazawal, Prateek; Choukroun, Daniel; Benninghoff, Heike; Gill, Eberhard
Hardware-in-the-loop simulations of two interacting bodies are often accompanied by a time delay. The time delay, however small, may lead to instability in the hardware-in-the-loop system. The present work investigates the source of instability in a two spacecraft system model with a time-delayed contact force feedback. A generic compliance-device-based contact force model is proposed with elastic, viscous, and Coulomb friction effects in three dimensions. A 3D nonlinear system model with time delay is simulated, and the effect of variations in contact force model parameters is studied. The system is then linearized about a nominal state to determine the stability regions in terms of parameters of the spring-dashpot contact force model by the pole placement method. Furthermore, the stability analysis is validated for the nonlinear system by energy observation for both the stable and unstable cases.